LG240 English for Professional Communication Workshop organised by APB UiTM Perak Branch/ NoorAileen Ibrahim ... [et al.] - Ibrahim, NoorAileen; Idris, Sheema Liza; Abdul Rani, Muhd Syahir; Anuar, Nuramira; Mohd Nasir, Nur Fatima Wahida (2024)
The Academy of Language Studies UiTM Perak Branch or Akademi Pengajian Bahasa (APB) UiTM Cawangan Perak had organised the LG240 workshop on the 5th and 6th of February 2024 at the Ibnu Firnas meeting room. Beginning March 2024, APB UiTM Perak Branch will be offering a Bachelor’s degree programme which is LG240 Applied Language Studies (Hons.) English for Professional Communication. Puan Sheema Liza Idris the Ketua Pusat Pengajian (KPP) of APB UiTM Perak, Dr. Nuramira Anuar the Coordinator of LG240 of APB UiTM Perak, and Mr. Muhd Syahir Abdul Rani the Coordinator of APB UiTM Tapah campus had initiated this workshop to provide the latest information about LG240 to all the APB lecturers of UiTM Perak.